Glycoconjugates in Host-Helminth Interactions - Prasanphanich, Nina S.; Mickum, Megan L.; Heimburg-Molinaro, Jamie; Cummings, Richard D. (Frontiers in Immunology, 2013)
Helminths are multicellular parasitic worms that comprise a major class of human pathogens and cause an immense amount of suffering worldwide. Helminths possess an abundance of complex and unique glycoconjugates that interact with both the innate and adaptive arms of immunity in definitive and intermediate hosts. These glycoconjugates represent a major untapped reservoir of immunomodulatory compounds, which have the potential to treat autoimmune and inflammatory disorders, and antigenic glycans, which could be exploited as vaccines and diagnostics. This review will survey current knowledge of the interactions between helminth glycans and host immunity and highlight the gaps in our understanding which are relevant to advancing therapeutics, vaccine development and diagnostics.